Papillary muscle rupture due to acute myocardial infarction followed by cardiogenic shock, pulmonary edema, and acute renal failure - Ilić Radoje; Trifunović Zoran; Tišma Svetislav; Ristić-Anđelkov Anđelka; Veljović Milić (Vojnosanitetski Pregled)
Aim. The case of successful surgical treatment of anterolateral papillary muscle rupture due to acute myocardial infarction with cardiogenic shock, pulmonary edema and acute renal failure. Case report. A 62-year old male from Belgrade with chest pain, hypotension and a new heart murmur refused hospitalization at the Military Medical Academy. On the third day of his illness he was readmitted to MMA as an emergency due to hemoptysis. Examination revealed mitral valve anterolateral papillary muscle rupture. The patient, with signs of cardiogenic shock and acute renal failure, was immediately operated on. The surgery was performed using extracorporeal circulation. An artificial mitral valve was implanted, and myocardial revascularization accomplished with one venous graft of the left anterior descending artery. On the second postoperative day, hemodialysis was carried out due to acute renal failure. On the 28th postoperative day, the patient was discharged from the hospital being hemodynamically stable with normal renal function and balanced anticoagulation. The case is interesting in terms of unrecognized papillary muscle rupture that led to the development of cardiogenic shock, hemoptysis and acute renal failure. Conclusion. Papillary muscle rupture is a fatal complication of acute myocardial infarction. Early recognition and urgent surgical intervention were lifesaving in the case of complete papillary muscle rupture. Surgical treatment, regardless of high risk, is the procedure of choice.